2010
DOI: 10.3340/jkns.2010.48.3.207
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Wide-Necked Intracranial Aneurysms Using Balloon-Assisted Technique with HyperForm Balloon

Abstract: Objective : To assess the feasibility, safety, and effectiveness of the balloon-assisted technique with HyperForm balloon in the endovascular treatment of wide-necked intracranial aneurysms. Methods : A total of 34 patients with 34 wide-necked intracranial aneurysms were treated with endovascular coil embolization using balloonassisted technique with Hyperform balloon. Twenty-nine aneurysms (85.3%) were located in the anterior circulation. The group of patients was comprised of 16 men and 18 women, aged 33 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…In the previously reported series with the HyperForm balloon, the authors reported the balloon to be very stable [8,15,16,17]. In our experience, the stability of the TOBC during the first positioning and during inflation and deflation was very steady.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…In the previously reported series with the HyperForm balloon, the authors reported the balloon to be very stable [8,15,16,17]. In our experience, the stability of the TOBC during the first positioning and during inflation and deflation was very steady.…”
Section: Discussionsupporting
confidence: 54%
“…The safety and efficacy of different balloons (HyperForm; eV3 Inc. and Ascent, Codman Neurovascular) in the treatment of wide-necked cerebral aneurysms has previously been reported in the literature [8,15,16,17,24]. For the very first time in this series, we sought to determine the safety, efficacy and feasibility of the TOBC, which was launched by Stryker Neurovascular in 2013.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations